VISUALISASI DATA PENGAJUAN PENJUALAN SEMBAKO MENGGUNAKAN POWER BI - nabila, ariyani (PT. ZIVANA CENDEKIAWAN BANGSA, 2024)
Staple food or what is often abbreviated from the words nine basic ingredients are food or drink basic necessities for all Indonesian people. Examples include rice, oil, sugar, salt, eggs and many other things. Nine basic commodities (sembako) are nine types of basic needs of society according to the Decree of the Minister of Industry and Trade Number 115/MPP/Kep/2/1998 dated 27 February 1998. The Ministry of Trade issued Regulation of the Minister of Trade Number 27/M-DAG/PER/5/ 2017 concerning Determination of Reference Prices for Purchases by Farmers and Reference Prices for Sales by Consumers which came into effect on 16 May 2017. The list of nine basic ingredients, namely rice, sugar, cooking oil and butter, beef and chicken, chicken eggs, milk, onions and garlic, LPG gas and kerosene, and salt.